Characterization of reactive graphene oxide synthesized from ball – milled graphite: its enhanced reinforcing effects on cement nanocomposites. Issue 9 (2nd May 2016) - Kothiyal, N. C.; Sharma, Snigdha; Mahajan, Swati; Sethi, Sapna
Abstract: In this study, commercial graphite powder (GP) of particle size 100 micron was subjected to high energy ball-milling (HEBM) to produce ball-milled graphite powder (BMGP) of particle size 780 nm. Both GP and BMGP were converted to respective graphene oxides (GOs) (labeled as GO1 and GO2) using Hummer's method, which were then characterized using techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X- ray diffraction (XRD). GO1 and GO2 were then investigated for their effects on compressive strength of cement mortar matrix at different curing times of 7, 14, and 28 days. Effect of variation of concentration (ranging between 0.125 and 1.00 wt% of cement) of GO1 and GO2 on the strength of matrix was examined. Microstructures of GO1-cement mortar nanocomposite and GO2-cement mortar nanocomposite were studied after 28 days of curing using SEM. Obtained results show that addition of 1.00 wt% GO1 and GO2 showed best performance by increasing the strength to 63 and 78%, respectively, in comparison to the unreinforced control sample. Improved performance of GO2 was attributed to more number of reactive sites of GO nanosheets induced by ball-milling treatment of graphite precursor.